266 Growth Performance, Fecal Score, and Blood Immune Parameters of Nursery Pigs Challenged with Escherichia coli F18 Fed Canola Meal-based Diet. (7th May 2021) - Hong, Jinsu; Ariyibi, Samuel; Scaria, Joy; Dilberger-Lawson, Steven; Francis, David; Woyengo, Tofuko A
Abstract: Effects of dietary canola meal (CM) on growth performance, fecal score, and blood parameters of E. coli-challenged nursery pigs were investigated. Thirty-six pigs (initial body weight = 6.22 kg) weaned at 21 d of age were housed individually and fed 3 diets (12 replicates/diet) in randomized complete block design. The diets were corn-soybean meal-based diet without or with antibiotics (0.2% chlortetracycline and 0.2% tiamulin) or with CM (20%). The diets were fed in 2 phases; Phase 1: d 0 to 7, and Phase 2: d 7 to 21. Pigs were orally challenged with F18 strain of E. coli on d 7. Feed intake and body weight were measured on d 7, 14, and 21. Blood samples for measuring thyroid hormones were collected from each pig on d 7, 14, and 21. Blood samples for measuring white blood cells, immunoglobulins, and cytokine were collected on d 21. Fecal score was assessed daily. Dietary antibiotics increased (P < 0.05) ADG by 50%. Dietary SECM also increased (P < 0.05) ADG by 23%. Week 1 fecal score was unaffected by diet. However, during weeks 2 and 3, fecal score for diet with antibiotics was less (P < 0.05) than that for basal diet or diet with CM, which did not differ in fecal score. During weeks 1 and 2, serum tetraiodothyronine level for diet with antibiotics was less (P < 0.05) than that for basal diet or diet with CM, which did not differ in serum tetraiodothyronine level; week 3 serum tetraiodothyronine level was unaffected by diet. White blood cell count was reduced (P < 0.05) by dietary antibiotics, and tended to be reduced (P = 0.087) by dietary CM. In conclusion, dietary CM increased ADG and tended to reduce white blood cell count. Thus, dietary CM at 20% may improve the performance of pigs challenged with E. coli F18 partly by decreasing immune response.